Pressure field along the axis of a high-power klystron amplifier - Degasperi, F. T. [UNESP]; Verardi, S. L.L. [UNESP]; Motta, C. C. [UNESP] (My University, 2003)
The pressure field in a high-power klystron amplifier is investigated to scale the ionic vacuum pump used to maintain the ultra high-vacuum in the device in order to increase its life-time. The investigation is conducted using an 1.3 GHz, 100 A - 240 keV high-power klystron with five reentrant coaxial cavities, assembled in a cylindrical drift tube 1.2 m long. The diffusion equation is solved to the regime molecular flow to obtain the pressure profile along the axis of the klystron drift tube. The model, solved by both analytical and numerical procedures, is able to determine the pressure values in steady-state case. This work considers the specific conductance and all important gas sources, as in the degassing of the drift tube and cavities walls, cathode, and collector. For the drift tube degassing rate equals to q deg= 2×10-12 _mbar.L.s-1 cm-2 (degassing rate per unit area), to cavities qcavity=3×10 -13 mbar.L.s-1cm-2, to the cathode q cathode= 6×10-9_mbar.L.s-1 and to the collector qcollector= 6×10-9 _mbar.L.s-1, it was found that a 10 L.s -1 ionic vacuum pump connected in the output waveguide wall is suitable. In this case, the pressure obtained in the cathode is p cathode= 6.3×10-9 mbar, in the collector p collector= 2.7×10-9 mbar, and in the output waveguide p = 2.1×10-9 mbar. Although only the steady-state case is analyzed, some aspects that may be relevant in a transient situation, for instance, when the beam hits the drift tube walls, producing a gas burst, is also commented.